Characterization of a possible founder synonymous variant in TECTA in multiple individuals with autosomal recessive hearing loss. Issue 12 (2nd August 2022) - Chen, Robert; Diaz‐Miranda, Maria Alejandra; Aref‐Eshghi, Erfan; Hartman, Tiffiney R.; Griffith, Christopher; Morrison, Jennifer L.; Wheeler, Patricia G.; Torti, Erin; Richard, Gabriele; Kenna, Margaret; Dechene, Elizabeth T.; Spinner, Nancy B.; et al.
Abstract: Synonymous variants have been shown to alter the correct splicing of pre‐mRNAs and generate disease‐causing transcripts. These variants are not an uncommon etiology of genetic disease; however, they are frequently overlooked during genetic testing in the absence of functional and clinical data. Here, we describe the occurrence of a synonymous variant [NM_005422.4 ( TECTA ):c.327C>T, p.(Gly109=)] in seven individuals with hearing loss from six unrelated families. The variant is not located near exonic/intronic boundaries but is predicted to impact splicing by activating a cryptic splicing donor site in exon 4 of TECTA . In vitro minigene assays show that the variant disrupts the reading frame of the canonical transcript, which is predicted to cause a premature termination codon 48 amino acids downstream of the variant, leading to nonsense‐mediated decay. The variant is present in population databases, predominantly in Latinos of African ancestry, but is rare in other ethnic groups. Our findings suggest that this synonymous variant is likely pathogenic for TECTA ‐associated autosomal recessive hearing loss and seems to have arisen as a founder variant in this specific Latino subpopulation. This study demonstrates that synonymous variants need careful splicing assessment and support from additional testing methodologies to determine their clinical impact.